PEMBANGUNAN HUKUM DENGAN PENDEKATAN SOSIO-LEGAL - Hartono, Hartono (At-Tawazun, Jurnal Ekonomi Syariah, 2019)
True law is not born from empty and empty space, people as legal users participate in coloring the law itself. The socio-legal approach puts forward two aspects; First the ability to analyze each product of textual study legislation, the articles in the legislation and policy can be analyzed critically and explained the meaning and implications for legal subjects (including marginalized groups). Secondly, the ability to interact with other legal sciences is also the development of global law today. The use of the socio-legal approach is actually intended to gain a new understanding that the law is not monoistic but the law can be seen also interdisciplinary, some experts also see that the law has many faces, in line with the interdisciplinary study, in fact legal pluralism is true, this can be seen from the paradigm that he built namely legal pluralism is associated with the "law that moves" in the realm of globalization. Therefore it becomes very important to see globalization in the context of history and law can be present there. Therefore the logical consequences of the science of law from a scientific product are open for critical review, either to deny or strengthen it, science will develop rapidly when there is a dialogue and deny each other in the sense of not mutually denying but mutually justifying and advancing, this offer in fact what I want to convey above is the tendency of mainstrim law with the positivism paradigm by offering a socio-legal approach.